The relationship between pond habitat depth and functional tadpole diversity in an agricultural landscape - Queiroz, Cássia de Souza [UNESP]; da Silva, Fernando Rodrigues; Rossa-Feres, Denise de Cerqueira [UNESP] (The Royal Society, 2015)
One of the most important goals of biodiversity studies is to identify which characteristics of local habitats act as filters that determine the diversity of functional traits along environmental gradients. In this study, we investigated the relationship between the environmental variables of ponds and the functional trait diversity distribution of anuran tadpoles in an agricultural area in southeastern Brazil. Our results show that the functional trait diversity of frog tadpoles has a bell-curve-shaped relationship with the depths of ponds inserted in a pasture matrix. Because we are witnessing increasing human pressure on land use, simple acts (e.g. maintaining reproductive habitats with medium depth) can be the first steps towards preserving the diversity of Neotropical frog tadpole traits in agricultural landscapes.
Keywords: Anuran; Biodiversity loss; Land use; Pasture matrix; Traits